THE USE OF ACTIVE AND PASSIVE SENTENCES ON STUDENTS’ WRITING RECOUNT TEXT - Siswanto Siswanto (Universitas Indraprasta PGRI, 2021)
Abstract: Learning writing skills used the eleventh-grade students of SMK Tunas Harapan, Jelambar, Petamburan. In conducting this research, it is qualitative research using a survey method. Data were collected by population and sample observation, interview, a document study, data of the students. The research of evaluation of the active and passive sentences, the result of the students’ error are: the total error in using active sentences are 171 errors that consist of 34 errors or 19,88% error of misinformation, 92 errors or 53,88% error of omission, 43 errors or 25,14% error of addition, two errors or 1,66% error of misordering. The result of the students’ error are: the total error in using Passive sentences are 17 errors that consist of 5 errors or 29, 41% error of misinformation, six errors or 35,29% error of omission, six errors or 35,29% error of addition, 0 errors or 0% error of misordering, the process of teaching and learning Writing using Recount Text of the Active and Passive Sentences are effective and able to implement as an alternative way in teaching and learning processKeywords: active and passive sentences, students’ writing, recount text.